Awareness and Forgetting of Facts and Agents - Ditmarsch, Hans van; French, Tim (Proceedings of the 2009 IEEE/WIC/ACM International Joint Conference on Web Intelligence and Intelligent Agent Technology - Volume 03, 2009)
We propose various logical semantics for change of awareness. The setting is that of multiple agents that may become aware of facts or other agents, or forget about them. We model these dynamics by quantifying over propositional variables and agent variables, in a multi-agent epistemic language with awareness operators, employing a notion of bisimulation with a clause for `same awareness'. The quantification is over all different ways in which an agent can become aware (or forget).